The Legality and Legal Validity of Online Auctions: A Normative Study in the Era of Public Service Digitalization - Ni Komang Sri Oka Mariana Dewi; I Gede Agus Kurniawan (Faculty of Law, Universitas Pekalongan, 2025)
This research examines the legality and legal validity of online auctions within the framework of applicable laws and regulations, and assesses its consistency with the principles of administrative law and legal protection for the parties. The purpose of this study is to analyze whether the implementation of online auctions has an adequate legal basis and how the formal and material validity of online auctions is normatively guaranteed. This research uses juridical-normative method with statutory approach and conceptual approach. The data analysis technique is carried out qualitatively by reviewing relevant laws and regulations, including the Minister of Finance Regulation (PMK), the Regulation of the Public Procurement Policy Agency (LKPP), and other technical regulations for the implementation of online auctions. The novelty of this research lies in the normative evaluation of the convergence between positive law and the rapidly growing practice of digital auctions. The results show that although the implementation of online auctions has been accommodated in a number of regulations, there are still lacunae of norms and inconsistencies between regulations that have the potential to cause legal uncertainty. On the other hand, the legal validity aspect of online auctions is still considered not fully fulfilling the principles of transparency, accountability, and legal protection for participants. This study recommends the establishment of special regulations regarding online auctions in the form of laws or at least comprehensive government regulations, in order to strengthen the legal basis and ensure certainty and justice in the practice of online auctions in the digital era.